1981
DOI: 10.1159/000115243
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Approach of Activity and Mechanism(s) of Action of Drugs Used in Cerebral Metabolic Insufficiency

Abstract: The authors described an experimental approach, specially using oral administration, of drugs used in cerebral metabolic insufficiencies and its application to l-eburnamonine (l-EB). Administered orally, l-EB: (1) significantly increased the cerebral consumption of [14C]-deoxyglucose in normoxic mice; (2) decreased the fall in cerebral energy charge (ECP) of rats after an acute normobaric hypoxia, and (3) stimulated the glycolysis of red blood cells (RBC) in healthy volunteers (repeated administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Linee et al 21 have found that orally administered L-eburnamonine significantly increased the cerebral consumption of [ 14 C]deoxyglucose in normoxic mice, decreased the fall in cerebral energy charge of rats after an acute normobaric hypoxia and stimulated the glycolysis of red cells in healthy volunteers. There were increases in red blood cell ATP and 2,3-diphosphoglycerate contents suggesting increased red blood cell deformability.…”
Section: B L-eburnamonine (Vinburnine)mentioning
confidence: 99%
“…Linee et al 21 have found that orally administered L-eburnamonine significantly increased the cerebral consumption of [ 14 C]deoxyglucose in normoxic mice, decreased the fall in cerebral energy charge of rats after an acute normobaric hypoxia and stimulated the glycolysis of red cells in healthy volunteers. There were increases in red blood cell ATP and 2,3-diphosphoglycerate contents suggesting increased red blood cell deformability.…”
Section: B L-eburnamonine (Vinburnine)mentioning
confidence: 99%
“…Earlier structure–activity relationship (SAR) studies showed the effects of different changes in the structure of the eburnane skeleton. The cerebrovascular activity is closely related to a specific configuration, namely, the natural cis -(3 S ,16 S )-eburnane skeleton, which can be identified in 1 and 2 , as well as in (−)-eburnamonine (vinburnine, 3 ), the latter two compounds are also marketed as cerebrovasculars. (Figure ).…”
Section: Introductionmentioning
confidence: 99%